Inclusão de glicerina bruta a diferentes volumosos altera os parâmetros ruminais e a produção de gases in vitro de bovinos confinados - Paschoaloto, Josimari Regina [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; Almeida, Marco Túlio Costa [UNESP]; Fávaro, Vanessa Ruiz; Homem Junior, Antonio Carlos; Carvalho, Vanessa Barbosa de; Perez, Henrique Leal [UNESP] (FapUNIFESP (SciELO), 2016)
The increasing availability of crude glycerin from biodiesel production has generated great stock in the industries. To solve this problem, crude glycerin is being used as an energy source to replace corn in livestock diets. This study evaluated the effects of the association of crude glycerin (10% on DM of diets) with different roughages in Nellore cattle diets on ruminal pH and ammonia, degradability, digestibility of dry matter and nutrients, and greenhouse gas production. Six ruminally cannulated Nellore steers were assigned to a 6×6 Latin square design. The following treatments were evaluated: Hydrolyzed Sugarcane associated or not with crude glycerin, Corn Silage associated or not with crude glycerin or Tifton-85 Hay associated or not with crude glycerin. Association of crude glycerin with roughages did not affect the rumen ammonia concentration and pH and dry matter intake, but reduced the intake of NDF for diets with Hydrolyzed Sugarcane and Corn Silage and reduced the digestibility of DM, OM, NDF, EE, CNF and starch and decreased the effective degradation at the rate of 8% h-1 for diets with Tifton-85 Hay. The association crude glycerin with Hydrolyzed Sugarcane reduced the production of CH4 and CO2 in mL g-1 of DM. The inclusion of crude glycerin affects differently nutrient utilization in diets with Corn Silage, Hydrolyzed Sugarcane or Tifton-85 hay. Moreover, promotes mitigation of greenhouse gases in diets with Hydrolyzed Sugarcane. Association of crude glycerin with Corn Silage in Nellore cattle diets showed better conditions of ruminal fermentation and utilization of nutrients.
Inclusion of crude glycerin with different roughages changes ruminal parameters and in vitro gas production from beef cattle
Keywords: Biodiesel; Byproducts; Degradability; Digestibility